Effets Du Labour Mécanisé Successif Sur Le Statut Nutritif Du Sol Et Le Rendement Du Riz Pluvial Dans La Commune d’Abomey Calavi (Sud Bénin) - C. S, Atidegla; L.O., Sintondji; J., Hounkpe; E., Kpadonou (European Scientific Journal, ESJ, 2017)
The effects of mechanized plowing with power tiller and rotavator and that of the succession of production campaigns on the nutritive status of soil and the rice yield in pluvial system were studied in the low land of Dokomey in South of Benin. The methodological approach is based on field trials conducted during three successive production campaigns from 2014 to 2016 according to a split plot design with one factor (plowing).. Sampling and analysis of the physical and chemical soils’ parameters were done at the beginning and end of each campaign and also the weighing of harvested paddy. Results showed that the fertility of the plots which received mechanized plowing and that of their yields increased noticeably during each campaign and along all the campaigns than those which received manual plowing. For example, from campaign 1 to 3, the yields under mechanized plowing increased respectively of 35%, 37% and 39% more than those obtained under manual plowing. The same report was obtained for soils parameters where the contents of organic matters (OM), nitrogen (N), ratio C/N, cationic exchange capacity, assimilable phosphorus (Pass) and clay increased respectively of 31,63% ; 11,77% ; 13,39% ; 10,28% ; 6,03% et 3,74%.Moreover, the correlations study between yield and nutritive status of soil showed likewise a high dependence between those parameters and the obtained yields. This dependence was highly significant at the level of 0.1% for th mechanized plowing